2020
DOI: 10.3389/fmicb.2020.00723
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Neonatal-Mouse Model to Characterize Vaccines and Strategies for Overcoming the High Susceptibility and Severity of Pertussis in Early Life

Abstract: For neonates without maternal-immunity, mixed-vaccination schedules that include the aP-and OMVP-vaccines appear to be the most appropriate to induce protection in the pups. For offspring from immune mothers, to avoid blunting-effect, NI should be carried out with vaccines other than those applied during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…The failure of current Bp vaccines to prevent transmission and nasal colonization among infants demonstrates limitations of the previous models used to develop these vaccines and emphasizes the necessity of a better understanding of host interactions, especially in highly sensitive newborns ( 20 , 21 , 52 , 53 ). PTx appears to disrupt critical early responses unique to neonates, potentially explaining the specific sensitivity of neonates to Bp .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure of current Bp vaccines to prevent transmission and nasal colonization among infants demonstrates limitations of the previous models used to develop these vaccines and emphasizes the necessity of a better understanding of host interactions, especially in highly sensitive newborns ( 20 , 21 , 52 , 53 ). PTx appears to disrupt critical early responses unique to neonates, potentially explaining the specific sensitivity of neonates to Bp .…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the limitations of available models, our understanding of the neonatal response to Bp has resulted in few preventative options in the very young. Thus, extraordinary lengths are often taken to prevent infant exposure, for example by booster vaccinating all their potential contacts, a practice referred to as “cocooning” ( 20 , 21 , 24 )…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the higher the antibody titer against a pertussis-specific antigen in a sow, the lower the neonatal antibody response to this antigen in the piglets born to the sow (data not shown). This interference from maternal antibodies present at time of immunization (known as blunting) has been observed in neonatal mice as well as in humans (33)(34)(35). The ratio of the maternal antibodies to vaccine antigens determines the extent of the inhibition, because there may be sufficient B cell epitopes free from maternal antibodies to be bound by the infants' B cells (36).…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA). As we previously described (39), plates (Nunc A/S, Roskilde, Denmark) were coated with proteins from bacterial lysates at 3 µg/ml in 0.5 M carbonate buffer pH 9.5, by means of an overnight incubation at 4 ºC. Blocked plates with 3% milk in PBS (2h 37ºC) were incubated with serially diluted samples of mouse serum (1h 37ºC).…”
Section: Groupsmentioning
confidence: 99%